Estudo fitoquímico e da atividade biológica do extrato hexânico de galhos de Maytenus gonoclada (Celastraceae) - Fernando Cesar Silva (2010)
Phytochemical study and biological activity of Maytenus gonoclada, family Celastraceae, is part of a project being developed on plants used in folk medicine at the Núcleo de Estudo de Plantas Medicinais (NEPLAM), of the Departamento de Química (DQ) at Universidade Federal de Minas Gerais (UFMG). Phytochemical study of the hexane extract of stems of M. gonoclada resulted in the isolation of seven pentacyclic triterpenes: 3-oxofriedelane, 3-hydroxyfriedelane, 3,11-dioxofriedelane, 3,16-dioxofriedelane, 3-oxo-12-hydroxyfriedelane, 3-oxo-29-hydroxyfriedelane and 3-oxo-12,29-dihydroxyfriedelane; it also was isolated, two long chain fatty acids, oleic acid and palmitic acid, as well as steroids, -sitosterol. The chemical structures were determined by spectrophotometric methods (IR, MS, 1H NMR, 13C NMR, HSQC,HMBC and NOESY). One of the most important points of this research is that 3-oxo-12,29-dihydroxyfriedelane is a new compound.The study of biological activity consisted of antimicrobial activity, activity of the capacity to inhibit acetylcholinesterase and insecticide activity. Another relevant finding of this study shows that it was found antibacterial activity against Staphylococcus aureus, antifungal against Candida albicans, giardicidal against Giardia lamblia and insecticide against larvae of Tenebrio molitor (a plague that affects grain storage) for the hexane extract. The triterpene, 3-oxo-12-hydroxyfriedelane, was active against the yeast C. albicans and larvae of T. molitor. The triterpene, 3-hydroxyfriedelane showed moderate inhibitory activity againstacetylcholinesterase. The mixture of triterpenes, 3,11-dioxofriedelane and 3,16-dioxofriedelane was also active against larvae of T. molitor.